The Impact of Escape Room Based Learning Method on Problem Solving Ability of High School Students - Kanti Aldino Hadi; Aditi Verma (Yayasan Adra Karima Hubbi, 2025)
Background. Challenge-based learning such as escape rooms is increasingly popular as an alternative in education. This method is seen as improving students' critical thinking and collaboration skills. However, there has not been much research exploring its impact on students' problem-solving abilities at the secondary education level. Purpose. This study aims to investigate the impact of escape room-based learning methods on the problem-solving ability of high school students. The focus of the research is to evaluate the change in students' problem solving skills after participating in escape room-based learning. Method. This study used an experimental design with two groups: the experimental group that used the escape room method and the control group that followed the conventional learning method. Data was collected through pretest and posttest to measure changes in students' problem-solving abilities. Data analysis was carried out using a t-test to compare the results between the two groups. Results. The results showed that the experimental group that used the escape room experienced a significant improvement in problem-solving ability compared to the control group. Students in the experimental group showed higher engagement and better critical thinking skills after following this method. Conclusion. This study concludes that escape room-based learning methods are effective in improving the problem-solving skills of high school students. This research also provides evidence that challenge-based learning can improve students' engagement and their ability to deal with problems creatively and collaboratively.